Insecticidal effects of four plants extract against prostephanus truncatus (horn) (coleoptera: bostrichidae) in infested dried cassava chips (2011)
The biological activity of Azardiractita indica (neem leaves), Tetrapleura tetraptera (seeds), Piper guinensee (alligator pepper seeds) and Xylopia aethiopica (black pepper seeds) extracts surface treatment applied at two different concentrations to dried cassava chips (Esculenta manihot) against Prostephanus truncatus (Horn) to determine infestation rate via mortality and emergence of the pest and weight loss in the dried cassava chips were conducted. The Bio assay was conducted under temperature and relative humidity of 27±2 and 65±5%, respectively within an investigation period of 28 days. Out of the four plants extract A. indica has the best insecticidal properties, this was followed by P. guinensee, T. tetraptera and X. aethiopica in a descending order of efficacy.